Fitness Facility Staff Can Be Trained to Deliver a Motivational Interviewing-Informed Diabetes Prevention Program - Dineen, Tineke E.; Bean, Corliss; Cranston, Kaela D.; MacPherson, Megan M.; Jung, Mary E. (Frontiers in Public Health, 2021)
Background: Training programs must be evaluated to understand whether the training is successful at enabling staff to implement a program with fidelity. This is especially important when the training has been translated to a new context. This community case study evaluated the effectiveness of the in-person Small Steps for Big Changes training for fitness facility staff using the 4-level Kirkpatrick training evaluation model. Methods: Eight staff were trained to deliver the motivational interviewing-informed Small Steps for Big Changes program for individuals at risk of developing type 2 diabetes. Between August 2019 - March 2020, 32 clients enrolled in the program and were allocated to one of the eight staff. The Kirkpatrick 4-level training evaluation model was used to guide this research. Level one assessed staff satisfaction to the training on a 5-point scale. Level two assessed staff program knowledge and motivational interviewing knowledge/skills. Level three assessed staff behaviors by examining their use of motivational interviewing with each client. Level four assessed training outcomes using clients’ perceived satisfaction with their staff and basic psychological needs support both on 7-point scales. Results: Staff were satisfied with the training (M = 4.43; SD = 0.45; range = 3.86-4.71). All learning measures demonstrated high post-training scores that were retained at implementation follow-up. Staff used motivational interviewing skills in practice and delivered the program at a client-centered level (≥ 6; M = 6.34; SD = 0.83; range = 3.75-7.80). Overall, clients perceived staff supported their basic psychological needs (M = 6.55; SD = 0.64; range = 6.17-6.72) and reported high staff satisfaction scores (M = 6.88; SD = 0.33; range = 6-7). Conclusion: The Small Steps for Big Changes training was successful and fitness facility staff delivered a motivational interviewing-informed program. While not all staff operated at a client-centered level, clients perceived their basic psychological needs to be supported. Findings support the training for future scale-up sites. Community fitness staff represent a feasible resource through which to run evidence-based counselling programs.